Response of contained masonry infilled frames due to earthquake forces - Achar, M. Mahadev; Prakash, D.S.; Babu, R. Ramesh (Journal of Structural Engineering, 2024)
This study reports the details of the finite element analysis of RC frames with contained masonry infill subjected to earth quake forces. Un-reinforced masonry (URM) infill frames is the most widely used type of construction throughout the world. They are considered as non structural elements which is reasonable for the frames under gravity loads but the same is not true for the frames under seismic loads. Contained masonry as infill in RC frames provides better contact at the interface and higher out of plane strength and stiffness. Considering the seismic action on the frames which are likely to be subjected to in-plane as well as out of plane shaking, a research work has been carried out by the authors to investigate the seismic performance of RC frames with and without contained masonry infill panels using FEM computer program (ANSYS) and experimentally using the tri-axial shake table to evaluate the methods proposed in IS- 1893-2002 to calculate the fundamental natural frequency. The RC frames were designed and detailed as per relevant Indian Standard specifi cations such as IS 456-2000, IS 18930-2002 and IS 13920-1993. Based on the experimental and analytical investigations, the contained masonry infill panels significantly affect the lateral load resisting characteristics of the RC frames.